Impacts of Gender Inequality on Human Development Index in Asia: A Panel Data Fixed Effect Regression - Mansha, Muhammad; Manzoor, Asma; Sarwar, Kiran; Hussain, Saad Ullah (iRASD Journal of Economics, 2022)
Gender inequality is a big issue in Asia. The objective of this study is to explain empirically how gender inequality affects the human enlargement index in Asian countries based on the panel data from 1990-2018. We utilized panel data Fixed Effect regression in this study to quantify the impacts of gender inequality on human development across Asian countries. The selection of the Fixed Effects Model has been made after the Hausman test results. The results of the study expose that gender inequality significantly contributed to both the human development index and the non-income human development index but their relationship is negative. As for as the control variables are concerned, working population and trade openness positively contributed towards human development while inflation and unemployment negatively contributed towards human development in Asia.